Answer:
1
Step-by-step explanation:
x²-1²...it can be written as (x+1),(x-1)...surely you will get -1 and 1 as your zero
Answer:
6
Step-by-step explanation:
Answer:
In 2 years
Step-by-step explanation:
age right now 1,5,7,9
Let the number of years in which the sum of the ages of two of his children be twice the sum of the ages of the other two children=x
Therefore Age of the children after x years will be 1+x,5+x,7+x and 9+x
2[1+x + 5+x] = (7+x)+(9+x)
2[6+2x]= 7+9+x+x
12+4x=16+2x
4x-2x=16-12
2x=4
x=4/2=2
Let's verify if the answer is correct
-- Verify by substituting the value of x in this 2[1+x + 5+x] = (7+x)+(9+x)
2[1+2 + 5+2] = (7+2)+(9+2)
2[10]=9+11
20=20
Therefore 2 years is the answer